Environmental carrying capacity assessment of industrial growth center region - Mardiana, Mardiana; Tampubolon, Dahlan; Zen, Irina Safitri (EDP Sciences - Web of Conferences, 2023)
Sustainable economic development, especially in the industrial sector, is an essential agenda for improving the population's welfare. The problem is that land use for the industry is dominant compared to considerations of the carrying capacity. This study aims to analyze the carrying capacity of the environment, especially land and water, in the industrial growth centre region (WPPI) South Riau. This study will quantify the potential of WPPI and its impact on the environment using the ECC approach. Data analysis was carried out using quantitative and descriptive analysis methods. The quantitative method is used to analyze the carrying capacity of the environment, and the descriptive method is used to analyze the recommendations resulting from the calculation of the carrying capacity of the environment. The land for developing industrial areas is mainly peat domes and marine. The land's carrying capacity status experienced a deficit, namely the regencies of Indragiri Hilir, Indragiri Hulu and Kuantan Singingi. The need for raw water/clean water in industrial growth centres reaches 3,758 litres/second. The land-carrying capacity in the study area is dominantly low, and the water-carrying capacity is very low.